2015
DOI: 10.3348/kjr.2015.16.4.846
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Magnetic Resonance Imaging Characteristics of Prostate Tuberculosis

Abstract: ObjectiveTo describe the multiparametric magnetic resonance imaging (MRI) appearance of prostate tuberculosis.Materials and MethodsSix patients with prostate tuberculosis were analyzed retrospectively. The mean age of the patients was 60.5 years (range, 48-67 years). The mean prostate specific antigen concentration was 6.62 ng/mL (range, 0.54-14.57 ng/mL). All patients underwent a multiparametric MRI examination.ResultsThe histopathological results were obtained from biopsies in four men and from transurethral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…The presence of a prostatic abscesses, as in the present case, is an infrequent but characteristic finding and appears on MRI as a nodular area of intense diffusion restriction and peripheral enhancement ( 5 , 6 ).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The presence of a prostatic abscesses, as in the present case, is an infrequent but characteristic finding and appears on MRI as a nodular area of intense diffusion restriction and peripheral enhancement ( 5 , 6 ).…”
Section: Discussionsupporting
confidence: 62%
“…Imaging examinations may help in diagnostic elucidation, but there is also overlap with features of prostatic adenocarcinoma. A series of cases ( 6 ) suggested two imaging patterns on MRI: a nodular pattern, represented by several small nodules in the peripheral zone, usually markedly hypointense on T2-weighted images and no significant diffusion restriction and a diffuse pattern, in which the whole peripheral zone is affected by hypointense bands in T2, but less evident when compared to the nodular pattern ( 5 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with mycobacterial GP are mostly asymptomatic, with elevated PSA levels and indurated prostate at digital rectal examination, but because of its relative rarity, the MRI characteristics of infective GP caused by Mycobacterium tuberculosis or after intravesical BCG instillations have not been described extensively and only a few cases have been reported ( 1 , 2 ). GP is found in approximately 75% of patients after intravesical administration of BCG for superficial bladder cancer ( 3 ).…”
Section: Case Descriptionmentioning
confidence: 99%
“…GP chronic pattern is common, with low mean ADC value <1000, decreased signal on the ADC map images and isointense or decreased signal on high-b-value imaging (b>1200) ( 4 ) that could be differentiated by the intralesional ADC values, significantly lower in PCa, as suggested by Rais-Bahrami ( 5 ). Recent studies also demonstrated an acute pattern (less than six months prior to the mpMRI) of GP lesions, with lower signal intensity on T2-weighted imaging (T2WI) ( 1 ), decreased signal on the ADC map images ( 3 ) and increased signal on high-b-value imaging ( 5 ), that is indistinguishable from aggressive prostate cancer.…”
Section: Case Descriptionmentioning
confidence: 99%
“…Prostate tuberculosis appears as a diffuse, radiating area with streaky low signal intensity on T2-weighted MRI as referred to as the "watermelon skin" sign. 65,72,73 It can also appear as an enlarged heterogeneous prostate with small abscesses in advanced stages. Diffuse dystrophic calcifications may be seen with long-standing prostatic tuberculosis.…”
Section: Testis Epididymis Seminal Vesicles and Prostatementioning
confidence: 99%